Rancang Bangun Robot Amphibi Sebagai Sistem Monitoring Gorong-Gorong - Mustar, Muhamad Yusvin; Nugraha, Aditiyo Eka; Hidayat, Ahmad Imam; Zidni, Hasan; Oktaviani, Rara Dwi (Universitas Muhammadiyah Yogyakarta, 2017)
This research proposes a design and implementation of a culvert monitoring system, based on amphibious robots that resemble ship shapes. This robot, enable to work on land or on the surface of water. A robot control algorithm, based on Arduino microcontroller programming designed and modeled as human and robot interaction, so users can interact directly with the robot in movement control. The outputs generated on this monitoring system are images and sound. Images and sounds obtained from Mobius camera installed on the robot. The results of monitoring and control of robots is controlled wirelessly, so it can perform robot control and monitoring of long-distance culvert and different places. The system proposed in this study can be implemented and applied in real terms, as a system that can help and facilitate the monitoring of water tunnel